Design and build a negative linear regulator - You, JianFang (2018)
Most of the electrical appliances at home require a low and stable Direct Current (Dc) voltage to operate. The power source from the power socket is 230V Alternating Current (Ac), which is too high for the electrical appliances. This might cause damage to the electrical appliances if the input power is too high. Therefore, it is important to convert the high Ac source to become a low and stable DC source so that it can be used to power up electrical appliances. One of the example will be the laptop adapter. The main purpose of this report is to show how to design and built a negative linear regulator. First, using the transformer to step down the 230V main supply to a voltage range that is suitable for the electronic device voltage rating. Next, stepped down voltage will go through the rectifier circuit to filter off the positive portion of the sine wave. Next, using smoothing capacitor to smoothen the fluctuation in the voltage waveform to become a ripple voltage. Lastly, using regulator to obtain a stable voltage that is suitable to supply to the electrical appliances. The report will go in depth on how the different components function in the regulator circuit and the working principle.